Effects of faba beans with different concentrations of vicine and convicine on egg production, egg quality and red blood cells in laying hens. (29th December 2016) - Lessire, M.; Gallo, V.; Prato, M.; Akide-Ndunge, O.; Mandili, G.; Marget, P.; Arese, P.; Duc, G.
Abstract : The faba bean ( Vicia faba L.) is a potential source of proteins for poultry, mainly for laying hens whose protein requirements are lower than those of other birds such as growing broilers and turkeys. However, this feedstuff contains anti-nutritional factors, that is, vicine (V) and convicine (C) that are already known to reduce laying hen performance. The aim of the experiment reported here was to evaluate the effects of a wide range of dietary V and C concentrations in laying hens. Two trials were performed with laying hens fed diets including 20% or 25% of faba bean genotypes highly contrasting in V+C content. In Trial 1, faba beans from two tannin-containing cultivars, but with high or low V+C content were dehulled in order to eliminate the tannin effect. In addition to the contrasting levels of V+C in the two cultivars, two intermediate levels of V+C were obtained by mixing the two cultivars (70/30 and 30/70). In Trial 2, two isogenic zero-tannin faba bean genotypes with high or low V+C content were used. In both trials, a classical corn–soybean diet was also offered to control hens. Each experimental diet was given to 48 laying hens for 140 (Trial 1) or 89 (Trial 2) days. Laying performance and egg quality were measured. The redox sensitivity of red blood cells (RBCs) was assessed by measuring hemolysis and reduced glutathione (GSH) concentration in these cells. Egg weight was significantly reduced by the diets containing the highest concentrations of V+C ( P <0.0001) in Trial 1 and slightly reduced ( P <0.10) in Trial 2, but only weak linear relationships between egg weight and dietary V+C concentration were established. No negative effect of V+C level was observed for egg quality parameters. In contrast, certain parameters (i.e. Haugh units, yolk color) were improved by feeding low V+C diets (P < 0.05). Hemolysis of RBCs was higher in hens fed high V+C diets. A decrease in GSH concentration in RBCs of hens fed the highest levels of V+C was observed. Faba bean genotypes with low concentrations of V+C can therefore be used in laying hen diets up to 25% without any detrimental effects on performance levels or egg characteristics, without any risk of hemolysis of RBCs.